Neuroscience of Addiction Molecular Mechanisms and Potential Therapeutic Targets - Aejeeliyah Yousuf (Middle East Journal of Pure and Applied Sciences (MEJPAS), 2025)
Addiction is a chronic brain disorder characterized by compulsive substance use despite adverse consequences. This paper explores the molecular mechanisms underlying addiction, focusing on neurotransmitter systems such as dopamine, glutamate, and the endocannabinoid system, as well as genetic and epigenetic changes that reinforce addictive behaviors. Various therapeutic targets, including pharmacological interventions, gene therapy, epigenetic modulation, neuroimmune modulators, and emerging technologies like CRISPR-Cas9, are discussed as potential pathways to treat addiction. The paper emphasizes the need for personalized, multi-faceted approaches to effectively address the complexities of addiction and highlights the challenges in translating scientific advances into real-world treatment options. By integrating innovative strategies and targeting the core molecular drivers of addiction, this research offers a comprehensive understanding of potential interventions that could pave the way for more effective and sustainable recovery solutions.